(untitled) (African Journal of Science, Technology and Social Sciences, 2024)
Introduction: Hygiene practices are essential for maintaining public health and preventing the spread of infectious diseases. Mass media has the potential to influence individuals’ hygiene behaviors and attitudes, by reaching a wide and diverse audience simultaneously, mass media can effectively disseminate targeted hygiene-related messages, leading to improved knowledge. Therefore, the study aimed to assess the contribution of mass media to the adoption of good hygiene practices in Garba Tula sub-county. Methodology: The study employed a mixed method approach where the researcher incorporated both qualitative and quantitative approaches, with a sample size of 191, which included the household heads, public health officers, area chief, and religious leaders. The study was conducted between December 2022 and February 2023. The data was analyzed by use of SPSS (2022) and ANOVA. Results: The study identified media representation, lack of awareness, poverty, lack of water, and culture as some of the factors associated with poor hygiene practices in Garba Tula Sub County. The study found there was a moderate relationship (P=<0.001) between hygiene practices and the media. It was noted that a significant percentage of households depended on the media for hygiene messages. Conclusion: The study concluded that the physical parameters and opinion leaders significantly influenced the adoption of good hygiene practices in the Gabra-Tula sub-county. The study recommends that mass media be used exhaustively to aid in behavior change and creating awareness.